Analisis kesulitan siswa pada materi teorema Pythagoras ditinjau dari kemampuan numerik - Azfa Nur Aqilah; Attin Warmi; Hanifah Hanifah; Kiki Nia Sania Effendi (IKIP Siliwangi, 2026)
This study aims to analyze the difficulties of junior high school students in solving mathematics problems on the Pythagorean Theorem material in terms of numerical ability based on the limitations of specific studies on numerical barriers affecting students' accuracy in applying the Pythagorean concept. The approach used is qualitative with a case study method. The research subjects consisted of 24 ninth-grade students at an Islamic junior high school in East Karawang, selected through purposive sampling based on the subject teacher's recommendations regarding learning barrier characteristics. The instruments used were a numerical ability test, Pythagorean Theorem questions, and interview guidelines. The results showed that the majority of students had low numerical ability and experienced difficulties in various indicators, such as performing calculations, thinking logically, problem solving, and recognizing number patterns. Even students with high numerical ability still had difficulty determining the slant side in Pythagorean problems. These findings indicate the importance of considering numerical ability in the learning process to develop more targeted and personalized learning methods.